Microplastic Abundance in The Flesh, Gills, and Stomachs of Pelagic Fish in Muncar Water, Banyuwangi, East Java - Sonia Putri Maulidya; Syarifah Hikmah Julinda Sari; Mochamad Arif Zainul Fuad; Feni Iranawati; Sabine Matallana-Surget; Aida Sartimbul (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2025)
The accumulation of microplastics in fish has become a significant concern in Muncar Waters, East Java, particularly in Bali sardinella (Sardinella lemuru) and scad (Decapterus sp.), which are two of the main catch commodities. Fish samples were collected from local fishermen and analyzed in the laboratory using microscopic techniques to identify and classify microplastic particles based on type and color.  A total of 1,322 microplastic particles were detected across all samples, with the highest abundance in the flesh (39.86%), followed by gills (31.01%) and stomachs (29.12%). Fragments were the dominant microplastic type (76.70%), while fibers (15.58%) and films (6.73%) occurred in lower proportions.Purple-colored particles were the most abundant (57.75%), followed by red (11.72%) and transparent (9.00%) microplastics., indicating it is the most contaminated species. This condition is likely due to the degradation of plastic materials, which enter the marine environment through various anthropogenic activities, including improper waste disposal, fishing gear degradation, and industrial runoff. This study highlights the need for improved waste management, stricter regulations, and community awareness to mitigate marine plastic pollution, contributing to the achievement of Sustainable Development Goals (SDGs) 2, 12, 14, and 15. The findings emphasize the urgent need for enhanced waste management practices, stricter regulations on plastic pollution, and increased public awareness regarding the risks of microplastic contamination. The research underscores the significance of consuming safe and nutritious food, promoting ocean conservation, encouraging responsible plastic consumption, and preserving marine biodiversity. Further investigation is necessary to understand the long-term effects of microplastic accumulation in fish and the related risks to the food chain, particularly in human health implications and ecological sustainability.